2015
DOI: 10.1016/j.cellsig.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

UCR1C is a novel activator of phosphodiesterase 4 (PDE4) long isoforms and attenuates cardiomyocyte hypertrophy

Abstract: Hypertrophy increases the risk of heart failure and arrhythmia. Prevention or reversal of the maladaptive hypertrophic phenotype has thus been proposed to treat heart failure. Chronic β-adrenergic receptor (β-AR) stimulation induces cardiomyocyte hypertrophy by elevating 3′, 5′-cyclic adenosine monophosphate (cAMP) levels and activating downstream effectors such protein kinase A (PKA). Conversely, hydrolysis of cAMP by phosphodiesterases (PDEs) spatiotemporally restricts cAMP signaling. Here, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…AKAP-Lbc is also implicated in cardiac hypertrophic signaling, and we have shown that AKAP-Lbc-tethered PKA is important for the induction of cardiomyocyte hypertrophy ( 13 ). Consistent with the observation that mice deficient in PKA-Cβ are resistant to hypertrophic stimuli ( 34 ), current data from our laboratory indicate that specific PKA inhibition abolishes ISO-induced cardiomyocyte hypertrophy, demonstrating the primary contribution of PKA ( 35 ). The results of this study demonstrate that the hypertrophic effect of ISO is inhibited by expression of the Shp2 T73A/S189A mutant, whereas expression of the T73D/S189D mutant significantly increases myocyte size in the absence of ISO stimulation.…”
Section: Discussionsupporting
confidence: 85%
“…AKAP-Lbc is also implicated in cardiac hypertrophic signaling, and we have shown that AKAP-Lbc-tethered PKA is important for the induction of cardiomyocyte hypertrophy ( 13 ). Consistent with the observation that mice deficient in PKA-Cβ are resistant to hypertrophic stimuli ( 34 ), current data from our laboratory indicate that specific PKA inhibition abolishes ISO-induced cardiomyocyte hypertrophy, demonstrating the primary contribution of PKA ( 35 ). The results of this study demonstrate that the hypertrophic effect of ISO is inhibited by expression of the Shp2 T73A/S189A mutant, whereas expression of the T73D/S189D mutant significantly increases myocyte size in the absence of ISO stimulation.…”
Section: Discussionsupporting
confidence: 85%
“…Notably, select PDE4Di's allosterically inhibit catalytic activity by promoting "trans-capping" (141); whereas, phosphatidic acid activates PDE activity by inhibiting trans-capping in a similar but mutually exclusive manner to PKA (223)(224)(225). Furthermore, the dominant negative peptide "UCR1C", which corresponds to UCR1 sequence, also activates PDE4 activity by inhibiting trans-capping (226). These results provide proof of principle that activation of PDE4 may be achieved by either small molecules or biologics that prevent UCR2 from adopting a trans-capping conformation.…”
Section: Activating Pdesmentioning
confidence: 99%
“…AKAP13 (also known as AKAP-Lbc) is a heart enriched anchoring protein expressed both in cardiomyocytes and cardiac fibroblasts [146,147]. This anchoring protein coordinates multiple signaling enzymes, such as PKA, protein kinase Cη (PKCη), protein kinase D1 (PKD1), PDE4D, phosphatases, and various MAPKs involved in the cardiac adaptation to stress and damage [148][149][150][151][152][153][154]. Unlike other AKAPs, AKAP13 also contains tandem Dbl homology (DH) and pleckstrin homology (PH) domains, which confer to the protein GEF activity towards RhoA and RhoC [146,155].…”
Section: Akap13mentioning
confidence: 99%